First study of the supernova remnant population in the Large Magellanic Cloud with eROSITA - Zangrandi, Federico; Jurk, Katharina; Sasaki, Manami; Knies, Jonathan; Filipović, Miroslav D.; Haberl, Frank; Kavanagh, Patrick; Maitra, Chandreyee; Maggi, Pierre; Saeedi, Sara; Bernreuther, Dominic; Koribalski, Bärbel S.; et al. (Astronomy & Astrophysics, 2024)
Aims. The all-sky survey carried out by the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board Spektrum-Roentgen-Gamma (Spektr-RG, SRG) has provided spatially and spectrally resolved X-ray data of the entire Large Magellanic Cloud (LMC) and its immediate surroundings in the soft X-ray band down to 0.2 keV, with an average angular resolution of 26′′ in the field of view. In this work, we study the supernova remnants (SNRs) and SNR candidates in the LMC using data from the first four all-sky surveys (eRASS:4). From the X-ray data, in combination with results at other wavelengths, we obtain information about the SNRs, their progenitors, and the surrounding interstellar medium (ISM). Studying the entire population of SNRs in a galaxy aids in understanding the underlying stellar populations, the environments in which the SNRs are evolving, and the stellar feedback on the ISM. Methods. The eROSITA telescopes are the best instruments currently available for the study of extended soft sources such as SNRs in an entire galaxy due to their large field of view and high sensitivity in the softer part of the X-ray band. We applied the Gaussian gradient magnitude filter to the eROSITA images of the LMC in order to highlight the edges of the shocked gas and find new SNRs. We visually compared the X-ray images with those of their optical and radio counterparts to investigate the true nature of the extended emission. The X-ray emission was evaluated using the contours with respect to the background, while for the optical, we used line ratio diagnostics and non-thermal emission in the radio images. We used the Magellanic Cloud Emission Line Survey for the optical data. For the radio comparison, we used data from the Australian Square Kilometre Array Pathfinder survey of the LMC. Using the star formation history derived from the near-IR photometry of the VISTA survey of the Magellanic Clouds, we investigated the possible progenitor type of the new SNRs and SNR candidates in our sample. Results. We present the most up-to-date catalogue of SNRs in the LMC. Previously known SNRs and SNR candidates were detected with a 1σ significance down to a surface brightness of Σ [0.2–5.0 keV] = 3.0 × 10−15 erg s−1 cm−2 arcmin−2 and were examined. The eROSITA data allowed us to confirm one of the previous candidates as an SNR. We confirm three newly detected extended sources as new SNRs, while we propose 13 extended sources as new X-ray SNR candidates. We also present the analysis of the follow-up XMM-Newton observation of MCSNR J0456–6533 discovered with eROSITA. Among the new candidates, we propose J0614–7251 (4eRASSU J061438.1−725112) as the first X-ray SNR candidate in the outskirts of the LMC.
CRIS-Team Scopus Importer:2025-02-04
Keywords: catalogs; galaxies: star formation; ISM: supernova remnants; Magellanic Clouds

New ASKAP radio supernova remnants and candidates in the Large Magellanic Cloud - Bozzetto, Luke M.; Filipovic, Miroslav D.; Sano, Hidetoshi; Alsaberi, R. Z. E.; Barnes, L. A.; Bojicic, I. S.; Brose, R.; Chomiuk, L.; Crawford, E. J.; Dai, Shi; Ghavam, M.; Haberl, F.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We present a new Australian Square Kilometre Array Pathfinder (ASKAP) sample of 14 radio supernova remnants (SNR) candidates in the Large Magellanic Cloud (LMC). This new sample is a significant increase to the known number of older, larger, and low surface brightness LMC SNRs. We employ a multi frequency search for each object and found possible traces of optical and occasionally X-ray emission in several of these 14 SNR candidates. One of these 14 SNR candidates (MCSNR J0522 - 6543) has multifrequency properties that strongly indicate a bona fide SNR. We also investigate a sample of 20 previously suggested LMC SNR candidates and confirm the SNR nature of MCSNR J0506 - 6815. We detect lower surface brightness SNR candidates which were likely formed by a combination of shock waves and strong stellar winds from massive progenitors (and possibly surrounding OB stars). Some of our new SNR candidates are also found in lower density environments in which SNe type Ia explode inside a previously excavated interstellar medium.
CRIS-Team WoS Importer:2023-01-27

Supernova remnants on the outskirts of the Large Magellanic Cloud - Sasaki, Manami; Zangrandi, Federico; Filipović, Miroslav; Alsaberi, Rami Z.E.; Collier, Jordan D.; Haberl, Frank; Heywood, Ian; Kavanagh, Patrick; Koribalski, Bärbel; Kothes, Roland; Lazarević, Sanja; Maggi, Pierre; et al. (Astronomy & Astrophysics, 2025)
When a star dies, it can explode in a supernova, causing a strong shock wave and forming an interstellar object called a supernova remnant (SNR). Observational studies of SNRs allow us to learn about the different types of progenitors, the explosion mechanisms, the physics of interstellar shocks, and the matter cycle in galaxies. We report on the first detection of SNRs located on the outskirts of a galaxy; namely, the Large Magellanic Cloud (LMC), the largest satellite galaxy of our Galaxy. The sources were discovered ∼3 outside the main stellar and gas distribution of the LMC in the recent surveys in radio with the Australian Square Kilometre Array Pathfinder (ASKAP) and in X-rays with the extended Roentgen Survey with an Imaging Telescope Array (eROSITA). We studied them in follow-up observations with the X-ray Multi-Mirror Mission-Newton telescope and MeerKAT and confirmed them to be SNRs. Their progenitors are most likely stars that had left the LMC due to tidal interaction between the Magellanic Clouds and the Milky Way. SNR J0614-7251 is located in an environment with a similar density to those of the other known SNRs in the LMC, and has similar X-ray properties. SNR J0624-6948, on the other hand, is located in a region with a lower density, n0 < 0.01 cm-3. Its radio shell shows a spectral index and polarisation typical of an SNR.
CRIS-Team Scopus Importer:2025-02-28
Keywords: ISM: supernova remnants; Magellanic Clouds; X-rays: individuals: SNR J0614-7251; X-rays: individuals: SNR J0624-6948; X-rays: ISM